Positive association between serum thymic stromal lymphopoietin and anti‐citrullinated peptide antibodies in patients with rheumatoid arthritis. (August 2015) - Koyama, K.; Ohba, T.; Haro, H.; Nakao, A.
Summary Thymic stromal lymphopoietin (TSLP) has been suggested recently to play an important role in the pathophysiology of rheumatoid arthritis (RA). However, there is little information on serum TSLP concentrations in RA and its clinical significance. The present study investigated whether serum TSLP concentrations were affected in patients with RA. Using an enzyme‐linked immunosorbent assay (ELISA), we measured TSLP concentrations in the serum obtained from 100 patients with RA, 60 patients with osteoarthritis (OA) and 34 healthy volunteers. We also investigated the correlation between serum TSLP concentrations and clinical parameters of disease activity in RA [disease activity score using 28 joint counts (DAS28)‐C‐reactive protein (CRP), DAS28‐erythrocyte sedimentation rate (ESR), Clinical Disease Activity Index (CDAI]), patient's/‐physician's Visual Analogue Scale (VAS), swollen joints count, tender joints count, CRP, ESR and matrix metalloproteinase‐3 (MMP‐3) concentrations]. In addition, we investigated the correlation between serum TSLP concentrations and anti‐citrullinated peptide antibody (ACPA) and serum tumour necrosis factor (TNF)‐α. Serum TSLP levels in patients with RA were significantly higher than those in patients with OA and in healthy volunteers. Interestingly, serum TSLP concentrations were correlated significantly with ACPA titres, but not with other clinical parameters. There was a significant increase in serum TSLP concentrations in patients with RA, which was correlated positively with serum ACPA titres. These findings suggest that in patients with RA, TSLP may play a role in ACPA production by B cells.